Joy Amid Ruin: More-than-human Literacies for Survival - Waliszewska, Aleksandra (Language and Literacy / Langue et littératie, 2025)
In this paper, I reflect on the past decade as an educator and graduate student to highlight the joy that accompanied my shifting understanding of literacy. I conducted an autobiographical narrative inquiry and used selections from blog entries and graduate coursework in order to reflect on my “moments of turning”. I begin with a logocentric understanding of literacy as a white settler in two Indigenous communities, but over time embrace a multimodal, embodied, emergent, place-based, and more-than-human conception of literacies within a context of the climate and nature emergency. This conception learns from and with Indigenous ways of knowing rooted in ecology, relationships, and the land. I argue that this understanding of literacies brings joy and opens possibilities in a precarious world.